Centre for the Development of Industry (CDI) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
Centre for the Development of Industry (CDI)The CDI is the sister organization of CTA: both institutes have been established within the framework of the Lom\E9 Convention. Whereas CTA's concern is with agricultural and rural cooperation, CDI's...